A Bottom‐Up Proteomic Approach to Identify Substrate Specificity of Outer‐Membrane Protease OmpT. (10th October 2017) - Wood, Sarah E.; Sinsinbar, Gaurav; Gudlur, Sushanth; Nallani, Madhavan; Huang, Che‐Fan; Liedberg, Bo; Mrksich, Milan
Abstract: Identifying peptide substrates that are efficiently cleaved by proteases gives insights into substrate recognition and specificity, guides development of inhibitors, and improves assay sensitivity. Peptide arrays and SAMDI mass spectrometry were used to identify a tetrapeptide substrate exhibiting high activity for the bacterial outer‐membrane protease (OmpT). Analysis of protease activity for the preferred residues at the cleavage site (P1, P1′) and nearest‐neighbor positions (P2, P2′) and their positional interdependence revealed FRRV as the optimal peptide with the highest OmpT activity. Substituting FRRV into a fragment of LL37, a natural substrate of OmpT, led to a greater than 400‐fold improvement in OmpT catalytic efficiency, with a k cat / K m value of 6.1×10 6 L mol −1 s −1 . Wild‐type and mutant OmpT displayed significant differences in their substrate specificities, demonstrating that even modest mutants may not be suitable substitutes for the native enzyme.